Improved photovoltaic efficiency and amplified photocurrent generation in mesoporous n = 1 two-dimensional lead – iodide perovskite solar cells - Febriansyah, Benny (2020)
We utilized two organic dications containing, respectively, a pyridinium and an imidazolium core to construct new n = 1 (where n refers to the number of contiguous two-dimensional (2D) inorganic layers, i.e., not separated by organic cations) 2D lead–iodide perovskites 1 and 2. The former material exhibits a (100)- and the latter a very rare 3 × 3 (110)-structural type. Compared with primary ammonium functionality, their constituent ring-centered positive charges have lower charge density. As a result, [PbI6]4– interoctahedral distortions of the inorganic lattice in 1 and 2 are reduced (Pb–I–Pb bond angles are as high as 166° and 174°, respectively). This results in bathochromically shifted optical features. In addition, the compact nature of the dications produces extremely short lead–iodide sheet separations, with respective iodide–iodide (I···I) distances as small as 4.149 and 4.278 Å. These are among the shortest separations of adjacent lead–iodide layers ever reported for such materials. When crystallized as thin films on top of substrates, the resulting 2D perovskite layers do not adopt a regular growth direction parallel to the surface. Instead, the crystallites grow with no fixed orientation. As a consequence of their proximate inorganic distances and unusual crystallization tendencies, the resulting 2D perovskites exhibit low excitonic activation energies (93.59 and 96.53 meV, respectively), enhanced photoconductivity in solar cells, and unprecedented incident photon-to-current conversion rates of up to 60%. More importantly, mesoporous 2D layered perovskite solar cells with power conversion efficiencies of 1.43 and 1.83% were achieved for 1 and 2, respectively. These are the highest values obtained thus far for pure n = 1 lead–iodide perovskites and more than 20 times higher than those obtained for materials templated by more conventional cations such as phenylethylammonium (0.08%).